2016
DOI: 10.4018/jdm.2016010103
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Neuroscience in Information Systems Research

Abstract: This paper reviews cognitive neuroscience and several neurophysiological tools (e.g., fMRI, PET, EEG, MEG, and eye tracking). The strengths and weaknesses of such tools for information systems research are presented. The paper provides examples of existing cognitive neuroscience studies in varies areas, such as neuroeconomics, neuromarketing, and eye tracking. In addition, this paper provides an overview of brain areas that response to various mental processes, and discusses the localization and functionality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Eye tracking has been used in the last decade, especially in the field of neuromarketing [10][11][12][13][14][15][16]. Recently, research has emerged pointing to the possibilities of its application and use in the educational process [17][18][19][20] or virtual reality [21].…”
Section: Related Workmentioning
confidence: 99%
“…Eye tracking has been used in the last decade, especially in the field of neuromarketing [10][11][12][13][14][15][16]. Recently, research has emerged pointing to the possibilities of its application and use in the educational process [17][18][19][20] or virtual reality [21].…”
Section: Related Workmentioning
confidence: 99%
“…Hence, our result is consistent with those in the literature. Future research can draw on mindfulness theory and cognitive fit theory as well as neurophysiological tools to understand the challenges faced by users, particularly men versus women, in 2D and 3D hedonic environments (Chan et al, 2012;Poston & Kettinger, 2014;Zhao & Siau, 2016). Our results also show that women perceive greater telepresence than men, which could be attributed to women's greater abilities to perceive and feel their surroundings than men (Seegmiller & Epperson, 1987;Woehlke & Piper, 1980), according to Jung's Theory of Psychological Types.…”
Section: Discussionmentioning
confidence: 55%
“…Thus, women enjoy interacting with hedonic systems more than men because of the fit between women's affective characteristics and the hedonic nature of the systems. Future research can examine the affective and emotional dimensions of users using neurophysiological tools (Zhao & Siau, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Analogous studies may also be conducted by other tools used in neuroscience such as electroencephalography [114,115], magnetoencephalography, and facial recognition. Reviews and discussion on the usefulness of various neuroscience methods can be found, for example, in [116,117].…”
Section: Validation Studiesmentioning
confidence: 99%